2018
DOI: 10.24071/ijiet.v2i2.1509
|View full text |Cite
|
Sign up to set email alerts
|

Basic Tense Problems of the First Semester Students of English Language Education Study Program

Abstract: This paper investigated the problems of understanding basic or fundamental tenses in English grammar (the present tense, present continuous tense, present future tense, and present future continuous) that are faced by the first semester students of the English Language Education Study Program of Sanata Dharma University, Yogyakarta. Basic tenses in English grammar play a decisive role in various aspects related to learning English as the target language. Accordingly, it is essential to conduct a study on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A number of studies have tried to unpack the reasons why the students have difficulty learning the simple past tense. Wahyuningtyas & Bram (2018) in their study with the first semester students of Language Education students found that students had difficulty in remembering the formula of the tenses and that these formulas are hard to comprehend. Interestingly, these students admit that they rarely review their grammar lessons independently.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have tried to unpack the reasons why the students have difficulty learning the simple past tense. Wahyuningtyas & Bram (2018) in their study with the first semester students of Language Education students found that students had difficulty in remembering the formula of the tenses and that these formulas are hard to comprehend. Interestingly, these students admit that they rarely review their grammar lessons independently.…”
Section: Introductionmentioning
confidence: 99%